TANTANGAN DAN PELUANG IMPLEMENTASI KURIKULUM MERDEKA BELAJAR DI PERGURUAN TINGGI: STUDI KASUS DI JURUSAN PENDIDIKAN BAHASA ARAB UIN MATARAM - Yahya, Septian; Suparmanto, Suparmanto; Hidayatullah, Syarif; Humam Zakaria, Sadid; Miratin Latifah, Dzu; Asfiya, Taqiyyul (STAI Darul Qalam Tangerang, 2024)
The Merdeka Belajar curriculum is a policy from the Ministry of Education and Culture of the Republic of Indonesia that encourages students and lecturers to improve competence by conducting education-based collaborative activities outside the agency. Of course, this policy also goes through an adaptation process in its implementation in various universities, one of which is the State Islamic University of Mataram. This research was conducted to determine the opportunities and challenges of implementing the Independent Learning Curriculum with case studies in the Department of Arabic Language Education. Data collection was done by observation and interviews. After the data is obtained and processed, the researcher analyzes the problem descriptively with a qualitative approach. The results of the study show that lecturers in PBA Study Program have a good understanding of the learning concept of the Merdeka Belajar Curriculum and recognize the importance of developing skills for students.The Merdeka Belajar curriculum is a policy from the Ministry of Education and Culture of the Republic of Indonesia that encourages students and lecturers to improve competence by conducting education-based collaborative activities outside the agency. Of course, this policy also goes through an adaptation process in its implementation in various universities, one of which is the State Islamic University of Mataram. This research was conducted to determine the opportunities and challenges of implementing the Independent Learning Curriculum with case studies in the Department of Arabic Language Education. Data collection was done by observation and interviews. After the data is obtained and processed, the researcher analyzes the problem descriptively with a qualitative approach. The results of the study show that lecturers in PBA Study Program have a good understanding of the learning concept of the Merdeka Belajar Curriculum and recognize the importance of developing skills for students. However, the challenges faced in implementing the independent learning curriculum include changing learning paradigms, integrating curriculum policies with existing organizational structures, changes in student assessment and evaluation, and developing supporting resources such as technology and facilities. Meanwhile, most students still need a clearer understanding of how to develop these skills and apply them in their learning context. This study aims to examine how the impact of the Merdeka Belajar Curriculum in universities. This study provides insight for educators, lecturers, and students in facing challenges and taking advantage of opportunities for the implementation of the Merdeka Belajar Curriculum at the Merdeka Belajar Campus